Lyme Carditis: An Interesting Trip to Third-Degree Heart Block and Back - Maxwell Eyram Afari; Fady Marmoush; Mobeen Ur Rehman; Umama Gorsi; Joseph F. Yammine (Case Reports in Cardiology)
Carditis is an uncommon presentation of the early disseminated phase of Lyme disease. We present the case of a young female who presented with erythema migrans and was found to have first-degree heart block which progressed to complete heart block within hours. After receiving ceftriaxone, there was complete resolution of the heart block in sequential fashion. Our case illustrates the importance of early recognition and anticipation of progressive cardiac conduction abnormalities in patients presenting with Lyme disease.